Istihsan in Bay’ Al-Istijrar: Recontextualising Ibn ʿAbidin’s Thought for Contemporary Mu’amalah Contracts - Enang Hidayat; Siti Ropiah; Mowafg Abrahem Masuwd (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2025)
Abstract: Debates on Bay’ al-Istijrār often revolve around permissibility of take now pay later arrangements, yet the decisive tension lies in the method of istiḥsān and the limits of gharar, especially regarding price certainty and the moment a contract is formed. A normative Islamic law inquiry at the level of doctrine applies conceptual, historical, and philosophical approaches, using document study based on Radd al-Muḥtār ʿalā al Durr al Muḥtār Sharḥ Tanwīr al-Abṣār as the primary source for bayʿ al-istijrār and Nasamāt al Ashār as a supporting source for istiḥsān. Ibn ʿĀbidīn’s argument frames the permissibility of Bay’ al-Istijrār not as an unregulated appeal to habit, but as istiḥsān that operates after naṣ, ijmā’, and qiyās are examined. Contract formation is understood to occur with each act of taking the goods, so the subject matter exists at the moment of sale and defined price must be knowable at the time of taking. End of period calculation functions as a settlement record, not as a device to postpone price certainty. ‘Urf serves to clarify practical standards when it qualifies as ‘urf ṣaḥīḥ and does not conflict with naṣ, while ‘urf fāsid is rejected because it expands uncertainty. Recontextualisation to contemporary muʿāmalah is directed toward technical tests of price standards, proof of delivery, rules on unilateral price changes, and accessible dispute resolution, so istiḥsān supports facilitation without sacrificing certainty. Abstrak: Perdebatan bai’ al-istijrār sering berkutat pada status kebolehan akad ambil dulu bayar kemudian, padahal titik perdebatan yang lebih menentukan berada pada metode istiḥsān dan batas gharar, terutama pada kepastian harga dan momen terbentuknya akad. Artikel ini mengkaji hal tersebut dari sisi hukum Islam normatif pada ranah doktrin menggunakan pendekatan konseptual, dengan teknik studi dokumen atas Radd al Mukhtār ʿalā al Durr al Mukhtār Sharḥ Tanwīr al Abṣār sebagai sumber utama baiʿ al istijrār dan Nasamāt al Ashār sebagai penguat pembahasan istiḥsān. Argumentasi Ibnu ʿĀbidīn menegaskan bahwa kebolehan baiʿ al-istijrār tidak disandarkan pada kebiasaan tanpa kontrol, melainkan pada istiḥsān yang bekerja setelah jalur naṣ, ijmā’, dan qiyās diperiksa. Akad dipahami lahir setiap kali pengambilan barang terjadi, sehingga objek hadir pada saat akad dan kepastian harga wajib dapat diketahui pada momen pengambilan barang. Perhitungan pada akhir periode diposisikan sebagai rekap pelunasan, bukan ruang untuk menunda kepastian harga. ‘Urf berperan sebagai penjelas standar praktik selama berstatus ‘urf ṣaḥīḥ dan tidak menabrak naṣ, sementara ‘urf fāsid ditolak karena memperluas ketidakpastian. Rekontekstualisasi dalam muamalah kontemporer diarahkan pada uji teknis atas standar harga, bukti serah terima, aturan perubahan harga, dan mekanisme penyelesaian sengketa, sehingga istiḥsān menjaga kemudahan tanpa mengorbankan kepastian.